Role of Herbs in the Management of Asthma - Prasad, Ranjeeta; Lawania, Rahul Dev; M, Manvi; Gupta, Rajiv (Pharmacognosy Reviews)
Herbs have been the highly esteemed source of medicine throughout human history. They are widely used today indicating that herbs are a growing part of modern, high-tech medicine. About 25-30 percent of today's prescription drugs contain chemical moieties derived from plants. The Indian system of medicine i.e Ayurveda alongwith classic texts like Bheshajya Ratnavali has a long-standing tradition that offers a unique insight into comprehensive approach to asthma management through proper care of the respiratory tract. Ayurvedic formulations used in the management of asthma, therefore, judiciously combine herbs to support the physiology of respiration, these herbs apart from exerting bronchial action also possess concomitant properties like antioxidant to support the digestive, cardiac, nerve functions and expectorant as well as just plain soothing herbs. Scientifically explored exhaustive reports have been published in Indian and International journals. Some of these herbs and their active chemical constituents which have a role in the management of asthma are compiled here and discussed in this review.
Keywords: Asthma; Herbs